Analysis of influencing factors on wellbore instability for high-pressure gas well during testing and production - Jiang, Hailong; Chen, Mian; Hua, Chao; Li, Xiao; Zhang, Yong (Frontiers in Earth Science, 2023)
Unlike normal-pressure gas wells, wellbore instability is more likely to occur during testing for high-pressure gas wells. Gas acceleration effect exists in gas flow during high-pressure gas well testing, which was ignored in previous wellbore instability analysis. In this paper, the developments of effective circumferential stress and effective radial stress are analyzed in the near-wellbore area of high-pressure gas well, considering the influence of in-situ stress non-uniformity and acceleration effect. To analyze the effective circumferential stress and the effective radial stress more accurately, it is established that the fluid-structure coupling stress field of the finite large thick wall cylinder The flow field considers three cases, namely Darcy’s law, Darcy–Forchheimer model and Darcy-Forchheime model considering gas acceleration. The results show that in-situ stress non-uniformity has a similar influence on tensile failure and shear failure. It is observed that the location of occurring shear failure and tensile failure may not be on the wellbore wall. When the formation fluid is under abnormally high pressure, it is more likely to have a tensile failure, while when the formation fluid is under abnormally low pressure, it is more likely to have a shear failure. The Biot parameter has the same effect on tensile failure and shear failure. These results are helpful to control sand production during testing and production for high-pressure gas wells.